Biological and Pharmacological Activity of Plant Natural Compounds II - Pezzani, Raffaele; Vitalini, Sara (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Special issue "Biological and Pharmacological Activity of Plant Natural Compounds II" is continuing the intriguing research on the use of natural plant products. The second edition follows the aim of the first one.